2016
DOI: 10.1136/bmjopen-2015-010429
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in glaucoma prescribing trends in England 2008–2012: an observational ecological study

Abstract: ObjectivesTo explore (1) the national trend in population-adjusted prescription rates for glaucoma and ocular hypertension (OHT) in England and (2) any geographical variation in glaucoma/OHT prescribing trends and its association with established risk factors for primary open-angle glaucoma (POAG) at the population level.DesignObservational ecological study.SettingPrimary care in England 2008–2012.ParticipantsAll patients who received 1 or more of the 37 778 660 glaucoma/OHT prescription items between 2008 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
(39 reference statements)
3
10
0
Order By: Relevance
“…Moreover, the preferred drug had been changed and combination therapy became a more favorable option. Prescription of glaucoma medications showed an upward trend between 2013 and 2017, which was basically consistent with previous reports in the literature [10]. An increasing Trends of glaucoma drug prescriptions number of patients with glaucoma was also revealed in another study [3].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the preferred drug had been changed and combination therapy became a more favorable option. Prescription of glaucoma medications showed an upward trend between 2013 and 2017, which was basically consistent with previous reports in the literature [10]. An increasing Trends of glaucoma drug prescriptions number of patients with glaucoma was also revealed in another study [3].…”
Section: Discussionsupporting
confidence: 89%
“…This has considerably lowered the cost for PGAs, and the conclusion is consistent with previous research in other regions (Heng et al. 2016).…”
Section: Discussionsupporting
confidence: 91%
“…2008; Connor & Fraser 2014; Heng et al. 2016). The increase in prescriptions might have several causes.…”
Section: Introductionmentioning
confidence: 99%
“…Geographical variations in prescription rates for glaucoma and ocular hypertension have been studied in England. 18 Cassard et al performed one of the largest national studies in the United States to elucidate the heterogenous distribution of glaucoma diagnosis across various regions. 19 They found that there were substantial regional differences in diagnosed rates for all types of glaucoma, even after adjusting for patient characteristics and provider concentration, suggesting possible over diagnosis in some areas and/or under diagnosis in other areas.…”
Section: Discussionmentioning
confidence: 99%